The Effect of Brand Equity and Customer Value in Repeat Visits of the Patients at Dr. Gunawan Mangunkusuma Regional General Hospital - Putri, Maria Novencia Dwi Armita; Farida, Naili; Arso, Septo Pawelas (Journal of Public Health for Tropical and Coastal Region, 2023)
Introduction: Patient visits at dr. Gunawan Mangunkusuma Regional General Hospital in 2020-2021 has increased by 9.78%. However, there is a decrease in the level of patient satisfaction with the services provided. This study aims to examine whether brand equity and customer value with the mediating factor of customer satisfaction affect repeat visits of the patients to dr. Gunawan Mangunkusumo Regional General Hospital. Methods: This type of research is a quantitative approach. The time of the study was in July 2022. The sample in the study was 185 patients using a purposive sampling technique. Linearity analysis in this study was carried out using SmartPLS.Results: The results showed that brand equity had a positive effect on patient satisfaction with a t-count of 4.006 > 1.96 (p<0.05). Brand equity has a positive effect on patient repeat visits with at value of 2,449 > 1.96 (p <0.05). Customer value has a positive effect on patient satisfaction with a t-value of 10,889 > 1.96 (p <0.05). Customer value also has a positive effect on patient repeat visits with a t value of 2,247 > 1.96 (p <0.05). Patient satisfaction has a positive effect on repeat visits of the patients with a t value of 2,869 > 1.96 (p <0.05). The mean repeat visits of the patients variable is 3.76. There are still indicators with a mean <3.76, namely RV1 and RV4Conclusion: The conclusion from this study is that brand equity and customer value greatly influence patient satisfaction and patient satisfaction greatly influences repeat visits. The hospital should be more aggressive in promoting the existence of the hospital to the community, assessing the suitability of prices paid by patients with the services received, reviewing service procedures at the hospital, and improving the HR department that handles patients so that customer satisfaction increases and repeats visits as well increase.